High performance SERS active substrates fabricated by directly growing graphene on Ag nanoparticles. Issue 110 (22nd October 2015) - Xu, Shicai; Wang, Jihua; Zou, Yan; Liu, Hanping; Wang, Guiying; Zhang, Xiumei; Jiang, Shouzhen; Li, Zhen; Cao, Dongyan; Tang, Rongxia
Abstract : An efficient surface enhanced Raman scattering (SERS) substrate of graphene-isolated Ag nanoparticle (G/AgNP) has been developed by using excimer laser to ablate the ordered pyrolytic graphite in high vacuum onto Ag nanoparticles. Abstract : An efficient surface enhanced Raman scattering (SERS) substrate of graphene-isolated Ag nanoparticle (G/AgNP) has been developed by using excimer laser to ablate the ordered pyrolytic graphite in high vacuum onto Ag nanoparticles. By combining the electromagnetic activity of AgNPs and unique physical/chemical properties of graphene, the G/AgNP substrates shows high performance in terms of sensitivity, signal-to-noise ratio and reproducibility. The average enhancement factor obtained from the G/AgNP substrates for rhodamine 6G probe molecules is over 10 8 . The maximum deviations of SERS intensities from 20 positions of a same SERS substrate are in the range of 4.20% to 6.75% and from 20 different substrates in various batches are in the range of 4.43% to 7.71%, depending on different vibration modes. As a practical application of this SERS system, we detect the adenosine concentration in human serum. The detection results show a good linear correlation between SERS intensity and adenosine concentration within the range of 2 to 200 nM. This work may open up new opportunities in developing the applications of SERS in biomedical diagnostics, biological sensing and other biotechnology.